2006
DOI: 10.1007/s00464-005-0407-z
|View full text |Cite
|
Sign up to set email alerts
|

Intrathoracoscopic localization techniques

Abstract: No ideal localization technique is available; thus, the choice still depends on surgeon's preference and local availability of both specialists and instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
56
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 79 publications
(99 reference statements)
1
56
0
Order By: Relevance
“…In contrast with conventional lung-marking techniques, which usually involve the placement of visible markings near an invisible or hardly palpable tumor (2), lung mapping provides "geometric information" on the lung's surface by placing multiple dye markings bronchoscopically (1,3) (Figure 1). Because of the very low risk of pneumothorax with this technique (3-4%), and the anatomical liberty available during bronchoscopic marking (3,4), the "map" drawn with VAL-MAP not only helps to identify the tumor, but also helps to determine oncologically appropriate resection lines.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with conventional lung-marking techniques, which usually involve the placement of visible markings near an invisible or hardly palpable tumor (2), lung mapping provides "geometric information" on the lung's surface by placing multiple dye markings bronchoscopically (1,3) (Figure 1). Because of the very low risk of pneumothorax with this technique (3-4%), and the anatomical liberty available during bronchoscopic marking (3,4), the "map" drawn with VAL-MAP not only helps to identify the tumor, but also helps to determine oncologically appropriate resection lines.…”
Section: Introductionmentioning
confidence: 99%
“…Controversy regarding its use is based on: (a) the falsenegative rate, which is as high as 29% [17] and approaching 60% among patients with nonspecific benign cytological findings [18]; (b) an incidence of pneumothorax of up to 30%, although only a minority of patients require further treatment [17][18][19][20][21][22] (chest tube in 5%-7% of cases developing pneumothorax); and (c) philosophically, many physicians consider the technique as superfluous and expensive and as an intermediate step with potential morbidity and only a small impact on definitive treatment [23][24][25].…”
Section: Diagnosis Of Indeterminate Pulmonary Nodulesmentioning
confidence: 99%
“…It has been reported that percutaneous biopsy avoids the need for subsequent surgery in only about 10% of patients who are physiologically able to directly undergo surgical resection [23]. In fact, if the lesion is proven to be malignant, surgery is indicated; if the lesion is diagnosed as nonspecific benign, surgical excisional biopsy is also considered.…”
Section: Diagnosis Of Indeterminate Pulmonary Nodulesmentioning
confidence: 99%
“…and avoid the morbidity associated with open thoracotomy [1]. A limitation of VATS is that small nodules or nodules located deeper within the lung parenchyma are difficult to visualize [2].…”
mentioning
confidence: 99%